2 USM PhD STUDENTS PAVING THE WAY INTO RESEARCH COLLABORATIONS WITH THE CZECH REPUBLIC - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 1 September 2016 – Universiti Sains Malaysia (USM) is creating history in its expansion of international collaborations by establishing its firstever research collaboration with one of the Czech Republic universities.